Dampak Lingkungan Kerja, Budaya Organisasi, dan Etika Kerja Islam terhadap Kinerja Karyawan - Anisa Amaliani; Irmayanti Hasan (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to determine the effect of work environment, organizational culture, and Islamic work ethics on employee performance at Bank Syariah Indonesia Hasanudin Jakarta branch. The method used is quantitative method and causal associative approach, namely to determine the effect of independent variables on the dependent variable. The analysis technique uses multiple linear regression analysis with SPSS software version 21. The data used are primary data and secondary data. Primary data collection was obtained from observations made by the author while carrying out field work practices for one month, followed by interviewing one of the employees, and distributing questionnaires related to the research topic to all employees with a saturated sample technique of 40 respondents. Secondary data collection is obtained from literature studies and documentation related to the research topic. The results of this study are partially work environment and organizational culture have no significant effect on employee performance. Meanwhile, partially Islamic work ethics has a significant effect on employee performance. Then, simultaneously work environment, organizational culture, and Islamic work ethics have a significant effect on employee performance at BSI KC. Jakarta Hasanudin..